STRATEGI PENGELOLAAN ADMINISTRASI KESISWAAN UNTUK MENINGKATKAN KEDISIPLINAN DAN KETERLIBATAN SISWA - Syafrina, Riska Nur; Hasanah, Siti; Andriego , Johan; Rizani, Loqman; Aulia, Nurul; Afriani, Nur; Dwihari, Desmarita (STKIP Pesisir Selatan, 2025)
Education is not only oriented towards mastering academic material, but also aims to shape students' character, one of which is through discipline and active involvement in school activities. This article aims to explain the importance of student administration management strategies in improving student discipline and involvement. Student administration is an integral part of educational management that includes various activities such as student data management, guidance and counseling, extracurricular activities, and monitoring student behavior. This study uses a literature review approach by analyzing various book references and scientific articles. The results of the discussion show that organized student administration is able to create an orderly, conducive school climate that supports the learning process. The strategies implemented include the implementation of a digital-based data management system, strict supervision of student attendance and behavior, and student involvement in school organizations such as OSIS. This strategy has proven effective in fostering disciplined character and increasing student involvement, which ultimately has a positive impact on academic and non-academic achievement. Therefore, good student administration management is the key to realizing holistic and character-based education.